The Importance of Digital Literacy to Enhance Students' ability in English Language - Made Hening Ayu Ayu Arsari (Jambura Journal of English Teaching and Literature, 2022)
The pandemic in Indonesia views that Indonesian people are still experiencing “technology stuttering”, especially in the education field, where technology is very rare due to the availability of technology devices. The phenomenon of pandemic situations makes it hard for teachers and students to carry online learning because they do not have adequate skills to implement online learning. It affects the quality teaching process and students outcomes in school, especially in English Language subjects. This research aims to observe the ability of senior high school student’s digital literacy skills in Singaraja, Bali. This research informed by descriptive qualitative employed semi-structured interviews to investigate 21 students. These interviews included the use of digital literacy skills in English Language Learning, and the results of interviews will be discussed in the paper. Digital literacy skills are the student’s ability to search information on the Internet. Moreover, with digital literacy skills, students can select the information carefully. This research shows the student’s ability in low level, and students cannot find information to support their learning process. Also, this research explains the importance of digital literacy skills, especially for ESL students and how to utilize digital literacy for the English language in the post-pandemic situation in Indonesia